3 Loop Structure based Fuel Flow Controller Design for Robust Operation of Ducted Ramjet Rocket - Srivastava, Srikant; Dwivedi, P.N.; Vinod Kumar, D.M. (Defence Science Journal, 2021)
This paper is about the designing of 3-loop structure based fuel flow controller (FFC) for efficient operation of supersonic ramjet based propulsion system. The main objective of the control design is to vary appropriately the engine controllable parameters (throttle value area) such that commanded thrust is achieved by ramjet engine without endangering the engine stability and performance. Various factors such as combustion-intake interaction, atmospheric disturbance and other flight conditions have a significant impact on the air intake operation which lead to effect on engine performance. Due to above effect, intake un-start and buzzing phenomena can occur due to back pressure fluctuation and it disturb the intake pressure recovery and air mass flow rate. So, back pressure based extra loop introduce in 2-loop FFC design to have tight control on back pressure margin for smooth and efficient operation of air intake without need of extra hardware.